2022
DOI: 10.1111/and.14553
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound heterozygous variants of DNAH17 in a Chinese infertile man with multiple morphological abnormalities of sperm flagella

Abstract: Multiple morphological abnormalities of the sperm flagellum (MMAF) have been reported to be an important cause of male infertility and reflect a heterogeneous genetic disorder. Previous studies have identified dozens of candidate pathogenic genes for MMAF, but the aetiology in approximately 50% of cases remains unexplained. The present study aimed to identify novel potentially pathogenic gene variants of MMAF. A Chinese family with a 32‐year‐old infertile proband presenting with MMAF was recruited, and sperm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent study has reported that FSIP2 mutant sperm show a globozoospermia phenotype in addition to flagella defects, and FSIP2 localizes in the acrosome and interacts with proteins associated with acrosome formation, indicating the potential function of FSIP2 in acrosome development ( Zheng et al, 2022 ), which is consistent with single-cell RNA-seq data ( Fang et al, 2021 ). FSIP2 has been demonstrated to interact with two other FS proteins, namely, AKAP3 and AKAP4, which are encoded by MMAF causative genes ( Zhang G. et al, 2021 ; Liu Z. et al, 2022 ). In 2005, the possible relationship between DFS and partial deletions in the AKAP3 and AKAP4 genes was revealed ( Baccetti et al, 2005b ).…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%
“…A recent study has reported that FSIP2 mutant sperm show a globozoospermia phenotype in addition to flagella defects, and FSIP2 localizes in the acrosome and interacts with proteins associated with acrosome formation, indicating the potential function of FSIP2 in acrosome development ( Zheng et al, 2022 ), which is consistent with single-cell RNA-seq data ( Fang et al, 2021 ). FSIP2 has been demonstrated to interact with two other FS proteins, namely, AKAP3 and AKAP4, which are encoded by MMAF causative genes ( Zhang G. et al, 2021 ; Liu Z. et al, 2022 ). In 2005, the possible relationship between DFS and partial deletions in the AKAP3 and AKAP4 genes was revealed ( Baccetti et al, 2005b ).…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%